Answer:
[tex]y = -x - 7[/tex].
Step-by-step explanation:
Slope of the given line segment:
[tex]\begin{aligned} m_{1} = \frac{(-5) - (-1)}{(-6) - (-2)} = 1\end{aligned}[/tex].
The slope of any line perpendicular to this line segment would be:
[tex]\begin{aligned}m_{2} &= \frac{-1}{m_{1}} = -1\end{aligned}[/tex].
Midpoint of the given line segment:
[tex]\displaystyle \left(\frac{(-2) + (-6)}{2},\, \frac{(-1) + (-5)}{2}\right)[/tex].
Simplifies to get:
[tex](-4,\, -3)[/tex].
Find the equation of the perpendicular bisector in point-slope form and simplify.
[tex]y - (-3) = (-1)\, (x - (-4))[/tex].
[tex]y + 3 = -x - 4[/tex].
[tex]y = -x - 7[/tex].